Mulher-Gato: políticas da mulher, modos de presença e narrativa transmídia - Fonseca, Thaís Silva (2016)
This research investigates the problematics of female representation in superheroes comic books having as object of research the anti-heroine Catwoman and how her modes of presence are marked by an objectified body that emphasizes the aesthetic dimension over the subjective. The study’s main question is to understand how the values that placed her in the position of sexual object and romantic partner of the hero Batman changed in her current representation due to the transmedia storytelling phenomenon and the participatory culture. At first, this research aims to explore the history of women in comics through the historical, social and cultural context of the years 1940 to 2010 and comprehend what influences these events had in the narrative construction and mutation of the female characters. Seeks, in a second moment, understand how the body is dealt by the enunciator, and analyze the changes of Catwoman’s dressed body. This analysis seeks to comprehend how the female construction in this media occurs and, therefore, enable a deconstruction of the hegemonic and sexist vision of what is to be a woman, and more specifically, of what is to be female character in the universe of comics. The methodological approach is through the semiotic analysis of the main costumes of Catwoman in comics, ranging from the 1940’s to 2010. Lastly, based on this analysis, is intend to compare the character’s modes of presence in comics with her narratives in other media platforms and realize how the participatory culture has influenced the democratization of the characters development. Thus, the research aims to contribute to a critique of the cultural industry in analyzing woman’s policies in communication relations through the comics and the transmedia storytelling. The research is supported theoretically in authors like Vergueiro (2003), Madrid (2009), Oliveira (2007); in sociosemiotics analysis, fashion and identity studies and the concept of dressed body of Oliveira (2005, 2008), as well as in Landowski regimes of visibility (1992); in gender policy analysis of Mulvey (1983); in the study of the media convergence phenomenon of Jenkins (2009) and the extremities reading of Mello (2008, 2016)